Imperial Eagle in the Republic of Tatarstan – Continuation of Research - Rinur H. Bekmansurov; Nadezhda V. Bekmansurova; Gennady N. Isakov (Пернатые хищники и их охрана)
Eastern Imperial Eagle (EIE Aquila heliaca) biology has been continuously studied in the Republic of Tatarstan (area 68,000 km2) since autumn of 2011 and covered some habitats in cross-border areas. In general, this is the area around the confluence of two largest rivers of the Eastern Europe, the Volga and Kama, and a number of their tributaries, and also belongs to the northern part of EIE breeding range in the Volga region. Research results up to 2018 were briefly presented at the previous conference “Eagles of the Palearctic” in 2018.